Teacher practice and the pre-crime space: prevent, safeguarding and teacher engagement with extremism and radicalisation. Issue 1 (2nd January 2019) - Revell, Lynn
ABSTRACT: School involvement in government initiatives to combat radicalisation is an international phenomena, in the UK government has focused on the role of the teacher in detecting radicalisation through the Teachers' Standards of 2012, the Counter Terrorism Act 2015 and the activation of Prevent in 2011. The Prevent Duty has been described as a geographical pre-crime space characterised by surveillance, risk, fear and the notion of the pre-criminal. This article explores the way teachers understand their practice in this pre-crime space. The data discussed in this study is part of a larger study that interrogates the way teachers approach the teaching of Islam in schools. This article reports on a series of dialogical interviews and analyses the way 57 teachers with a particular responsibility for Religious Education have negotiated this new role. It argues that teachers commonly situate their practice in relation to Prevent in the context of a safeguarding agenda and that most legitimise their role through the employment of a discourse of vulnerability. The research suggests that the ways teachers approach issues of extremism in the classroom is in part informed by their existing views on racism, social class and political ideologies.